Correction: Surface alignment of ferroelectric nematic liquid crystals. Issue 27 (1st July 2022) - Caimi, Federico; Nava, Giovanni; Barboza, Raouf; Clark, Noel A.; Korblova, Eva; Walba, David M.; Bellini, Tommaso; Lucchetti, Liana
Abstract : Correction for 'Surface alignment of ferroelectric nematic liquid crystals' by Federico Caimi et al., Soft Matter, 2021, 17, 8130–8139, ; https://doi.org/10.1039/D1SM00734C .